MEMBACA DUNIA SUREALIS IBW. WIDIASA KENITEN DALAM KUMPULAN CERPEN BUDUH NGELAWANG - I Wayan Juliana (Kalangwan Jurnal Pendidikan Agama, Bahasa dan Sastra, 2021)
Buduh Ngelawang's short story collection is one of the literary works that was bornfrom the hands of a teacher named IBW. Widiasa Keniten. Apart from being a teacher, he isalso active in writing literary works in both Balinese and Indonesian. His works should beappreciated and given comments in order to add to the repertoire of literary criticism in thefield of modern Balinese literature itself. In Buduh Ngelawang's short story collection, theauthor builds a new world in modern Balinese literature that has never been done before. Theauthor offers a new model in structuring the modern Balinese literary form, namely the surrealform. On this occasion, Buduh Ngelawang's short story collection will be analyzed based onTzevetan Todorov's narratological structure theory. In the narratological analysis, thesemantics (in absensia) aspect will be discussed. The semantic aspect relates to the involvementof denotative meaning and connotative meaning as a way to express meaning.